Casa Turull exhibition display (circa 1950) - Hercules Incorporated (1950)
General view of a Spanish-language exhibition display advertising a range of chemical products intended for agricultural use, including insecticides and disinfectants manufactured by Casa Turull and the Hercules Powder Company. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Advertising; Advertising, Industrial; Corporations; Chemical industry; Agricultural chemicals; Agricultural chemicals industry; Insecticides; Livestock; DDT (Insecticide)